Microencapsulated natural food colourants in Malaysia - Yus Aniza, Yusof, Engr. Assoc. Prof.; Chong, Pik Han (The Instituition of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org